Orthostatic Tremor Responds to Bilateral Thalamic Deep Brain Stimulation. (20th February 2012) - Lyons, Mark K.; Behbahani, Mandana; Boucher, Orland K.; Caviness, John N.; Evidente, Virgilio Gerald H.
Background: Orthostatic tremor (OT) is a disabling movement disorder manifested by postural and gait disturbance. Primarily a condition of elderly people, it can be progressive in up to 15% of patients. The primary treatments are medications that are often ineffective. Case Report: A 75-year-old male presented with a 10-year history of progressive and disabling OT. He had tried various medications without significant benefits. He underwent bilateral thalamic Vim deep brain stimulation (DBS). At 30-month follow-up, he has had continued significant improvement of his OT. Discussion: Bilateral thalamic DBS may be a viable option for medically refractory OT.